Construction of a circRNA-miRNA-mRNA Regulated Pathway Involved in EGFR-TKI Lung Adenocarcinoma Resistance. (November 2021) - Dai, Chenyue; Liu, Bing; Li, Shaolei; Hong, Yang; Si, Jiahui; Xiong, Ying; Wu, Nan; Ma, Yuanyuan
Objectives: Epidermal growth factor receptor-tyrosine kinase inhibitors are widely used for lung epidermal growth factor receptor-positive lung adenocarcinomas, but acquired resistance is inevitable. Although non-coding RNAs, such as circular RNA and microRNA, are known to play vital roles in epidermal growth factor receptor-tyrosine kinase inhibitor resistance, comprehensive analysis is lacking. Thus, this study aimed to explore the circular RNA-microRNA-messenger RNA regulatory network involved in epidermal growth factor receptor-tyrosine kinase inhibitor resistance.Methods: To identify differentially expressed genes between the epidermal growth factor receptor-tyrosine kinase inhibitor sensitive cell line PC9 and resistant cell line PC9/ epidermal growth factor receptor-tyrosine kinase inhibitor resistance(PC9/ER), circular RNA, microRNA and messenger RNA microarrays were performed. Candidates were then identified to construct a circular RNA-microRNA-messenger RNA network using bioinformatics. Additionally, Gene Oncology and Kyoto Encyclopedia of Genes and Genomes pathway analyses were conducted to evaluate the network messenger RNA, setting up a protein-protein interaction network for hub-gene identification. Afterwards, RNA immunoprecipitation was performed to enrich microRNA, and quantitative real-time PCR was used to estimated gene expression levels.Results: In total, 603, 377, and 1863 differentially expressed circular RNA, microRNA, messenger RNAs, respectively, were identified using microarray analysis, constructing a circular RNA-microRNA-messenger RNA network containing 18 circular RNAs, 17 microRNAs and 175 messenger RNAs. Moreover, Gene Oncology and Kyoto Encyclopedia of Genes and Genomes pathway analyses showed that the most enriched biological process terms and pathways were related to epidermal growth factor receptor-tyrosine kinase inhibitor resistance, including Wnt and Hippo signaling pathways. Based on the competing endogenous RNA and protein-protein interaction network, circ-0007312 was showed to interact with miR-764 and both circ-0003748 and circ-0001398 were shown to interact with miR-628; both these microRNAs targeted MAPK1. Furthermore, circ-0007312, circ-0003748, circ-0001398, and MAPK1 were up-regulated, whereas miR-764 and miR-628 were downregulated in PC9/ER cells as compared to parental PC9 cells. We also found that circ-0007312 and miR-764 were positively expressed in plasma.Conclusions: Our original study associated with mechanism of target therapy in lung cancer provided a systematic and comprehensive regulation of circular RNA, microRNA and messenger RNA in epidermal growth factor receptor-tyrosine kinase inhibitor resistance. It was found that circ-0007312- miR-764-MAPK1, circ-0003748-miR-628-MAPK1, and circ-0001398-miR-628-MAPK1 axis may play key roles in epidermal growth factor receptor-tyrosine kinase inhibitor resistance.